Property Appraisals with Multicriteria Analysis in Urban Buildings in the Historic Center of Cajamarca - Peru (LACCEI, 2024)
The present study is justified in the acquisition of real estate at present, its objective is to analyze the appraisal process applying the valuation methods by multicriteria analysis in the historic center of Cajamarca (ZT1) It is a non-experimental investigation, various methods are used in the data analysis process, the results will be developed according to the characteristics of the property to be appraised and the most probable market value, in order to demonstrate the multiple benefits of multicriteria analysis. In the multicriteria methods, the Baricentric method was analyzed, which gave us a value per square meter in a range of "1,485.31 U.S.$/m2" to "1,542.43 U.S.$/m2", by the Entropy method, a value of "1,491.89 U.S. $/m2", in the Diakoulaki method, a value of "1,491.80 U.S.$/m2", with the Weighted Sum method and applied to the Entropy method, a value per square meter of "1,467.76 U.S.$/m2" was obtained, and applied to the Diakoulaki method, the unit value is "1,491.42 U.S.$/m2". As a result, we conclude that the Manhattan distance method together with the Baricentric method helps us to improve the appraisal process by 98% effectively.